Respuesta :

Answer:

here is a formulae

cos2A= 2cos square a -1

Step-by-step explanation:

as given cos A= 1/2 (a+1/a)

by simplifying

cosA =a²+1/2a

now by following the formulae

cos2A = 2cos²A-1

=2(a²+1/2a)² -1

=2(a⁴+2a²+1/4a²)-1

=a⁴+2a²+1/2a² -1

=a⁴+2a²+1-2a²/2a²

=a⁴+1/2a²

=1/2 (a⁴+1/a²)

=1/2(a⁴/a²+1/a²)

=1/2(a²+1/a²)

{proved}

please mark me as a brainilist...plzzz

thank uuu

Answer:  see proof below

Step-by-step explanation:

Use the Double Angle Identity: cos 2A = 2cos²A - 1

Proof  LHS → RHS

Given:                                [tex]\cos A=\dfrac{1}{2}\bigg(a+\dfrac{1}{a}\bigg)[/tex]

LHS:                                   cos 2A

Double Angle Identity:      2(cos²A) - 1

                                     [tex]=2\bigg(\dfrac{1}{2}\bigg(a+\dfrac{1}{a}\bigg)^2\bigg)-1[/tex]

Simplify:                           [tex]2\bigg(\dfrac{1}{4}\bigg(a^2+2+\dfrac{1}{a^2}\bigg)\bigg)-1[/tex]

                                     [tex]=\dfrac{1}{2}\bigg(a^2+2+\dfrac{1}{a^2}\bigg)-1[/tex]

                                    [tex]=\dfrac{1}{2}a^2+1+\dfrac{1}{2a^2}-1[/tex]

                                    [tex]=\dfrac{1}{2}a^2+\dfrac{1}{2a^2}[/tex]

Factor:                         [tex]=\dfrac{1}{2}\bigg(a^2+\dfrac{1}{a^2}\bigg)[/tex]

[tex]\dfrac{1}{2}\bigg(a^2+\dfrac{1}{a^2}\bigg)=\dfrac{1}{2}\bigg(a^2+\dfrac{1}{a^2}\bigg)\quad \checkmark[/tex]

Ver imagen tramserran
Ver imagen tramserran
ACCESS MORE